White islands in a sea of red - Sara Elizabeth Milla Salguero; Eduardo Smelin Perdomo Domínguez (IDCases)
Dengue is a viral disease caused by a single-stranded RNA virus from the Flaviviridae family, primarily transmitted by the Aedes aegypti mosquito, although Aedes albopictus also plays a role as a vector. Clinical features of dengue range from nonspecific symptoms to severe forms like dengue shock syndrome. Among these clinical features, dermatological manifestations are particularly noteworthy, as they can aid in differentiating dengue from other illnesses.